INFLUENCE OF P-GLYCOPROTEIN AND CYTOCHROME ISOENZYME-P3A4 ON BIOAVAILABILITY OF ANTICANCER DRUGS WITH CURCUMIN BY IN SITU INTESTINAL PERFUSION IN MALE WISTAR RATS: Influence of P-glycoprotein & CYP3A4 on bioavailability of anti cancer drugs - MANOJ KANNA NALLA; SHANKARAIAH PULIGILLA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: An orally administered anticancer drug has been poor drug absorption; drug resistance and metabolism, which alters the bioavailability of drugs. An in situ intestine perfusion technique is developing under the different perfusion rates in the presence of drug inducers and inhibitors of cytochrome isoenzyme-P (CYP)-3A4 and P-glycoprotein (P-gp) for drug concentrations. Materials and Methods: The modified in situ intestinal perfusion technique was developed and followed to obtain the portal and hepatic venous blood samples paralleled at different perfusion time and flow rates of 0.05, 0.1, 0.5, and 1.0 mL/min using the imatinib (1 mg/mL) drug alone and in the presence of drug inducer and drug inhibitor for the period of 3 h. The imatinib drug concentrations were assayed using high-pressure liquid chromatography. Results: The results reveal that the mean imatinib drug concentrations in portal vein were higher than hepatic vein at various perfusion flow rates and time intervals were observed. The area under curve and plasma drug concentrations maximum of imatinib alone absorptions were significantly different between portal and hepatic veins (p<0.05) at the flow rates of 0.5 and 1.0 mL/min and also in the presence of drug inducer and inhibitors that indicating for the considerable hepatic involvement in the presystemic extraction or metabolism of drugs. Conclusions: The in situ perfusions approach could provide the useful tool for improving the basic understanding of absorption kinetics and hepatic metabolism of drugs in the presence of drug inducers and drug inhibitors (CYP3A4 and P-gp) under the development and facilitating the clinical applications.